Determinação de HPAs em amostras ambientais por pré-concentração em membrana de náilon, espectroscopia de fluorescência e calibração de segunda ordem - Siqueira, Alcides da Silva (2024)
Polycyclic Aromatic Hydrocarbons are compounds formed by condensed aromatic rings. Of the more than one hundred substances that make up this group, sixteen are monitored due to greater human exposure and because they are associated with respiratory, gastrointestinal, genitourinary, dermatological, and cardiovascular problems, as well as cancer. They are generated continuously by human activities such as oil refining, fires, fuel burning, among others. As they have an affinity for organic matter, soils or sediments are the main destinations for PAHs coming from the atmosphere. The determination of these compounds requires time-consuming chromatographic methods, with a high consumption of solvents, and presents a loss of light PAHs during the extraction and concentration stages of the organic extract. Solid-phase extraction on a nylon membrane followed by spectrofluorimetry with detection directly on the membrane and second-order calibration is a sensitive, fast, and low-cost alternative that allows the quantification of PAHs in simple matrices, mainly water. A limitation for membrane detection in more complex samples is that particles from the solution are retained on the membrane surface, compromising signal detection. This work presents an alternative for carrying out detections on the back of the membrane (opposite side to filtration), avoiding interference from particulate matter. For this, the polarity of the solvent and the elution of the analytes to the back of the membrane were studied. Membrane-back detection was applied to the simultaneous determination of anthracene, phenanthrene, and fluorene in drinking water in the concentration ranges of 0.4–2 µg L⁻¹, 0.8–7.2 µg L⁻¹, and 6–30 µg L⁻¹, obtaining average recoveries of 96%, 98%, and 104%, respectively. It was also applied to river sediment extracts in the concentration ranges of 30–90 µg kg⁻¹ (anthracene), 120–360 µg kg⁻¹ (phenanthrene), and 300–900 µg kg⁻¹ (fluorene), obtaining average recoveries of 93%, 91%, and 93%, respectively.